Ficções televisuais : ficções do fluxo : televisão e minimalismo em alguma prosa norte-americana e brasileira - Oliveira, Leandro Salgueirinho de (2010)
This thesis investigates the way two dominant cultural traits televisuality and minimalism merge together within certain American and Brazilian literature. In order to accomplish this it tries to understand what, during the 1980 s, certain authors tried to define as Image-fiction and/or TV Fiction, whilst understanding that these critical attempts maintained a close relationship with what is nowadays seen, retrospectively, as the minimalist debate in the field of American literature. It proceeds to analyze three North-American novels: White Noise (1985) by Don DeLillo, Peru (1986) by Gordon Lish and American Psycho (1991) by Bret Easton Ellis; the collection of short stories What We Talk About When We Talk About Love (1981) by Raymond Carver as well as two books by the Brazilian author André Sant Anna, Amor (1998) and Sexo (1999). The thesis has the objective of understanding how these texts relate with (more than) one notion of televisuality and the way that they unfold or even deviate from what I considered a minimalist poetics in its strict sense.